MODEL PENDIDIKAN ANAK USIA DINI PADA DAERAH PANTAI DI SULAWESI SELATAN - Daruma, Abd. Razak; Talib, Syamsul Bahri; Tetteng, Basti Tetteng (Indonesian Journal of Educational Studies, 2010)
Abstract: A Model for Early Childhood Education in Coastal Areas in South Sulawesi. This study aims at exploring the early childhood education in coastal areas in South Sulawesi. The research data were collected through focus group discussion, in-depth interviews, and documentation involving parents, kindergarten teachers, and community leaders. The results provided a description of the attitudes and knowledge of parents about early childhood, the activities of parents in educating their young children, parents’ ways of child rearing, parents treatment of health and nutrition of young children, and parents and government/ private institutions in supporting the implementation of early childhood education. Abstrak: Model Pendidikan Anak Usia Dini pada Daerah Pantai di Sulawesi Selatan. Penelitian ini bertujuan mengeksplorasi pendidikan anak usia dini pada daerah pantai di Sulawesi Selatan. Subjek penelitian adalah orang tua, guru TK, dan tokoh masyarakat. Pengumpulan data dilakukan dengan diskusi kelompok terarah, wawancara mendalam, dan dokumentasi. Hasil penelitian memberikan deskripsi sikap dan pengetahuan orang tua tentang anak usia dini, pelaksanaan kegiatan orang tua dalam mendidik anak usia dini, pola asuh orang tua, perlakuan orang tua terhadap kesehatan dan gizi anak usia dini, partisipasi orang tua/lembaga pemerintah/swasta dalam membantu pelaksanaan pendidikan anak usia dini. Kata Kunci: anak usia dini, sikap, pengetahuan